Analysis of immunoglobulin Sgamma3 recombination breakpoints by PCR: implications for the mechanism of isotype switching. - Du, J (1997)
The molecular mechanism of immunoglobulin switch recombination is poorly understood. Switch recombination occurs between pairs of switch regions located upstream of the constant heavy chain genes. Previously we showed that switch recombination breakpoints cluster to a defined subregion in the Sgamma3, Sgamma1 and Sgamma2b tandem repeats. We have developed a strategy for direct amplification of Smu/Sgamma3 composite fragments as well as Smu and Sgamma3 regions by PCR. This assay has been used to analyze the organization of Smu, Sgamma3 and a series of Smu/Sgamma3 recombination breakpoints from hybridomas and normal mitogen-activated splenic B cells. DNA sequence analysis of the switch fragments showed direct joining of Smu and Sgamma3 without deletions or duplications. Mutations were found in two switch junctions on both sides of the crossover point, suggesting that template switching is the most likely model for the mechanism of switch recombination. Statistical analysis of the positions of the recombination breakpoints in the Sgamma3 tandem repeat indicates the presence of two sub-clusters, suggesting non-random usage of DNA substrate in the recombination reaction.